Monitoring System of The Temperature for Mini Fish Storage using Internet of Things - Prayetno Eko (EDP Sciences, 2021)
Fish is one of the high-protein foods that are very helpful for the development of the human brain. Then, it is necessary to maintain the freshness of the fish for consumption. At this time, fishers and fishmongers preserve the freshness of fish by using Ice in the fish storage. However, it is considered ineffective due to improper ice change time. Therefore, monitoring temperature is very important and helpful to find the right time when replacing the Ice used to ensure the quality of fish. The development of this device uses Arduino ESP32, DHT21 Sensor, Micro SD Module, Internet of Things system, monitoring using Blynk Application and notifications using Telegram App. DHT21 sensor test results obtained a data conformity level (Error Level) of 2%. At the fish storage room temperature, there is the lowest temperature of 10.50 oC and ice temperature conditions in the storage of 0 oC. Therefore, the best state to keep fish fresh that researchers want is 0 oC to 2 oC at ice temperatures or 11.50 oC obtained in testing the time it takes to replace Ice by about 10 hours.